Pengaruh Ukuran Perusahaan, Anak Perusahaan, Profitabilitas, Leverage, dan Ukuran KAP terhadap Audit Delay (pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Puspitasari, Dwi Ninda; , Dr. Dra. Erma S., Ak., MM (2016)
This study aimed to examine the effect of size of the company, subsidiaries, profitability, leverage, size of public accountant firms to audit delay at manufacturing companies registered in Indonesian stock exchange. The selection of the sample used in this study is purposive sampling with a sample size of 114 companies acquired during the period 2012 -2014. Analysis of data using multiple linear regression analysis. The results of this research can be concluded that the subsidiaries, profitability, leverage, size of public accountant firms affect audit delay. While the size of the company have not affect the audit delay.